FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP PENDAPATAN DAN PRODUKTIVITAS AGROINDUSTRI GULA KELAPA DI KABUPATEN PANGANDARAN - Yuroh, Fitri; Maesaroh, Ida (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2018)
The purpose of this research is to know: (1) Income of coconut sugar agroindustry and its influencing factors, and (2) Productivity achieved in coconut sugar agroindustry and its influencing factors. The research was conducted by using survey method on 100 coconut sugar agroindustries in Pangandaran District. Coconut sugar agroindustry income is approached by using income analysis, while productivity is approximated by using total factor productivity. Factors affecting income and productivity were analyzed by using multiple regression equation. The results showed: (1) The total cost of coconut sugar agroindustry in Pangandaran Regency was Rp 85,135.39, Rp 113,232.00 in revenue, and Rp 28,096.61 in income. Total production, capital, education, credit, and extension have significant effect to coconut sugar agroindustry income, and (2) Total factor productivity achieved at coconut sugar agroindustry in Pangandaran District ranged from 0.60 to 3.12, with an average of 1.52. Production costs, education, experience, family size, credit, and extension have a significant effect on the productivity achieved in coconut sugar agroindustry.Keywords: Coconut Sugar, Income, Total Factor Productivity